Language Convergence to Build Social Harmony in the midst of Diversity: Evidence from Angantiga Village of Badung Regency, Bali - Ni Made Wiasti; Ida Bagus Putra Yadnya; Ni Made Dhanawaty (RETORIKA: Jurnal Ilmu Bahasa, 2022)
As a social being, people will socialize through communication using language as a medium. The decision to choose a language or use one of the language codes depends on the perceived cost or benefit he will get. This paper is intended to describe communication patterns and preferences for language use especially within a culture where another language is dominant. It is a sociolinguistic study using descriptive qualitative methods on the Muslim diaspora community in the village of Angantiga, Badung Regency who had lived in Bali province in Indonesia for more than a generation. The data were collected through questionnaires, in-depth interviews, and direct observation. The results show that there is a relationship between language use in various domains and self-identity. As a diaspora community they are very accommodating and show language tolerance to maintain communication and interpersonal relationships. The language convergence is carried out in order to seek approval or social recognition from the surrounding community. It can foster tolerance to build social harmony in the midst of diversity.